ORGANOLEPTIK PAHA ITIK MAGELANG DENGAN PERENDAMAN SARI BELIMBING WULUH (Averrhoa bilimbi L.) PADA KONSENTRASI BERBEDA - Muhammad Hilmi Hatta; Rahma Wulan Idayanti; Nur Hidayah (Jurnal Ilmu dan Teknologi Peternakan, 2022)
Duck thigh meat is part of the carcass which has the highest percentage, which is 26.8% carcass. Duck meat has a high fat and protein content, so the meat is easily damaged by microbes. Microorganism contamination in duck meat can reduce the quality of the meat, so it is necessary to handle it to maintain the quality of the meat. One of the natural preservatives that can be used to protect food from spoilage and physical damage is bilimbi fruit (Averrhoa bilimbi L.). This study aims to determine the best concentration of bilimbi fruit in the organoleptic physical properties of Magelang duck thigh meat. This study used Magelang ducks aged 2-3 months on the thigh and used a completely randomized design (CRD) with 4 treatments (concentration of starfruit juice 0, 20, 40, 60% v/v) and 5 replications. Observational were analyzed by means of variance (ANOVA) at a 5% significance level, then if there were differences between treatments, further DMRT test was performed. The results showed that the immersion at a concentration of bilimbi fruit of as much as 60% significantly changed the color to ash (2.88) and reduced the scent to a slightly fishy (3.59), taste parameters changed to sour (3.16-3.59) with a concentration of bilimbi fruit 40-60% and had no significant effect on the texture of the Magelang duck thigh meat. This study concluded that soaking 60% starfruit juice for 30 minutes was able to reduce the fishy aroma, make the pale color, and the taste becomes sour, but does not affect the texture of Magelang duck thigh meat.